2010
DOI: 10.3390/ijerph7093313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cytotoxic Assessment of Ballistic Aerosol Particulates for Tungsten Alloy Penetrators into Steel Target Plates

Abstract: The nature and constituents of ballistic aerosol created by kinetic energy penetrator rods of tungsten heavy alloys (W-Fe-Ni and W-Fe-Co) perforating steel target plates was characterized by scanning and transmission electron microscopy. These aerosol regimes, which can occur in closed, armored military vehicle penetration, are of concern for potential health effects, especially as a consequence of being inhaled. In a controlled volume containing 10 equispaced steel target plates, particulates were systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…There was no indication of elemental mixing of the target and tungsten heavy alloy (Fe and W, respectively). 6 Although the projectiles also contained about 8% (weight) of either Fe and Ni, or Fe and Co, there was no significant evidence of these elements either in combined (or alloyed) form or as single-component nanoparticulates in the collected aerosol, even though the nanoparticulate fraction collected on the filters dominated the particle concentration.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…There was no indication of elemental mixing of the target and tungsten heavy alloy (Fe and W, respectively). 6 Although the projectiles also contained about 8% (weight) of either Fe and Ni, or Fe and Co, there was no significant evidence of these elements either in combined (or alloyed) form or as single-component nanoparticulates in the collected aerosol, even though the nanoparticulate fraction collected on the filters dominated the particle concentration.…”
Section: Introductionmentioning
confidence: 91%
“…1,3,5 A recent study by Machado et al of filter collections representing aerosol debris resulting from heavy alloy tungsten, kinetic energy rod projectiles penetrating steel plate arrays in steel enclosures demonstrated the induction of rapid and complete death of a human epithelial cell type in culture. 6 This suggests that there may be a severe human toxicity potential for inhaled ballistic aerosol inside an armored vehicle penetrated by a variety of projectiles, particularly of tungsten heavy alloy rods into steel armor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the advantages for aerosol droplets with magnetic particles, the objective risk assessment studies have to be performed. Many of studies confirmed that the metal oxide particles are very toxic, especially in the pulmonary system (Machado et al, 2010). Nowadays, the in vitro studies are focused on the characterization and cytotoxic assessment of aerosol particulates, especially the nanoparticles based on heavy alloys W-FeNi and W-Fe-Co.…”
Section: External Magnetmentioning
confidence: 99%